2013
DOI: 10.1155/2013/967872
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Living with Diabetes Described by Family Members of Adult People with Type 1 Diabetes

Abstract: The aim of this study was to explore family members' experiences of everyday life in families with adult people living with type 1 diabetes. The grounded theory method was used to gather and analyse data from the interviews of nineteen family members. Six concepts describing the family members' views on everyday living with diabetes were generated on the basis of the data. Everyday life with diabetes is described as being intertwined with hypoglycemia. Becoming acquainted with diabetes takes place little by li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(57 citation statements)
references
References 44 publications
(60 reference statements)
0
52
0
5
Order By: Relevance
“…Trief et al (2017) reported that having an engaged partner was associated with better glycemic control (β = 0.13, p< 0.01) and self-care such as concordance with general diet (β = 0.22, p< 0.001) and exercise (β = 0.28, p< 0.01) (Trief et al, 2017). T1D partners supported self-management behaviours by reminding the PWD of blood glucose measurements (Rintala, 2017), encouraging exercise and supporting healthy eating habits for the whole family (Rajaram, 1997;Rintala et al, 2013b). To further support self-management, T1D partners in some cases bought the insulin and blood glucose testing materials (Barnard et al, 2016;Rintala et al, 2013b).…”
Section: Proms Used To Measure Relationship Satisfaction and Psycholomentioning
confidence: 99%
See 4 more Smart Citations
“…Trief et al (2017) reported that having an engaged partner was associated with better glycemic control (β = 0.13, p< 0.01) and self-care such as concordance with general diet (β = 0.22, p< 0.001) and exercise (β = 0.28, p< 0.01) (Trief et al, 2017). T1D partners supported self-management behaviours by reminding the PWD of blood glucose measurements (Rintala, 2017), encouraging exercise and supporting healthy eating habits for the whole family (Rajaram, 1997;Rintala et al, 2013b). To further support self-management, T1D partners in some cases bought the insulin and blood glucose testing materials (Barnard et al, 2016;Rintala et al, 2013b).…”
Section: Proms Used To Measure Relationship Satisfaction and Psycholomentioning
confidence: 99%
“…T1D partners supported self-management behaviours by reminding the PWD of blood glucose measurements (Rintala, 2017), encouraging exercise and supporting healthy eating habits for the whole family (Rajaram, 1997;Rintala et al, 2013b). To further support self-management, T1D partners in some cases bought the insulin and blood glucose testing materials (Barnard et al, 2016;Rintala et al, 2013b). In contrast, T1D partners' overprotective behavior was found to be associated with less frequent blood glucose measurement (β= 0.14, p< 0.05) (Trief et al, 2017).…”
Section: Proms Used To Measure Relationship Satisfaction and Psycholomentioning
confidence: 99%
See 3 more Smart Citations